Collecting duct carcinoma kidney masquerading as hydatid cyst: A rare case report and review of literature - Varsha Kumar; Vatsala Misra; Dilip Chaurasiya; Neelima Verma (Wolters Kluwer Medknow Publications, 2018)
Cystic renal masses pose diagnostic challenge especially when they belong to Bosniak Type II and III. Septal and nodular enhancement on computed tomography (CT) is the strongest predictor of malignant process. A unilocular cyst with a calcified rim or a multilocular cystic lesion with heterogeneity on CT goes in favor of hydatid disease. We report a case in a 65-year-old female who presented with painless hematuria, was found to have a cystic mass in the right kidney. The mass turned out to be collecting duct carcinoma after histopathological examination though imaging studies were in favor of a hydatid cyst.